Analisis Polifarmasi Terhadap Interaksi Obat Di Rumah Sakit Umum Kota Pekalongan - Permadi, Yulian Wahyu; Akrom; Imam Riadi; St Rahmatullah (Lembaga Bale Literasi, 2025)
The use of drugo in large quantities is called polypharmacy. The number of drug interactions depends on the number of drugs consumed, the possibility of drug interactions increases as more drugs are used in the prescription. This study aims to analyze the incidence of polypharmacy and drug interactions in outpatient prescriptions at Pekalongan City General Hospital. This study is a retrospective descriptive study conducted by analyzing outpatient prescription data for the period March–May 2023 at the hospital pharmacy depot. Prescription sheets containing two or more drugs (R/) were identified through reliable literature sources, namely www.drugs.com and www.medscape.com. Data were grouped and analyzed using SPSS spearman test. The results showed that of the total incidence of drug interactions of 877 patients, the gender of the patients was mostly female (68%), the age of the most was 26-45 years (58%), the number of drugs in the prescription was the largest two drugs with potential interactions 44%, the level of polypharmacy was moderate (48%), minor (21%), major (13%) and no interaction (18%). The largest number of diagnoses in the prescription was two diagnoses at 44%. The highest drug interaction mechanisms are pharmacodynamics (57.3%), pharmacokinetics (13%), unknown (29.7%). The most interacting drug combinations are rifampicin isoniazid 6.9%, furosemide cefixime 4.5% and sertraline gabapentin 4.5%. The correlation between the number of drug use and diagnosis according to the results of this study is a significant, strong and unidirectional correlation. Based on the results of this study, it is recommended that polypharmacy in prescriptions can be minimized and drug interaction monitoring be tightened to reduce the risk of dangerous side effects.